Conservation Laws

Two particles of masses m 1 m_1 and m 2 m_2 collide elastically in the x y xy -plane. Their initial velocities are ( u 1 x , u 1 y ) (u_{1x}, u_{1y}) and ( u 2 x , u 2 y ) (u_{2x}, u_{2y}) , respectively.

After the collision, the kinetic energy of Mass 1 is roughly five times that of Mass 2. Additionally, the x x -velocity of Mass 1 after the collision is v 1 x v_{1x}

After the collision, what is the y y -velocity of Mass 1?

Details and Assumptions:

  • ( m 1 , m 2 ) = ( 2 , 3 ) (m_1, m_2) = (2,3)
  • ( u 1 x , u 1 y ) = ( 3 , 5 ) (u_{1x}, u_{1y}) = (3,5)
  • ( u 2 x , u 2 y ) = ( 7 , 1 ) (u_{2x}, u_{2y}) = (-7,-1)
  • v 1 x = 5 v_{1x} = -5


The answer is 8.105.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Chew-Seong Cheong
Sep 22, 2018

Let the x x - and y y -components of momentum before collision be p x p_x and p y p_y respectively. Then p x = m 1 u 1 x + m 2 u 2 x = 2 ( 3 ) + 3 ( 7 ) = 15 p_x = m_1u_{1x} + m_2 u_{2x} = 2(3) + 3(-7) = - 15 . Since the collision is elastic, by conservation of momentum, p x p_x after collision is also 15 -15 . Therefore,

m 1 v 1 x + m 2 v 2 x = 15 2 ( 5 ) + 3 v 2 x = 15 v 2 x = 5 3 \begin{aligned} m_1v_{1x} + m_2v_{2x} & = -15 \\ 2(-5) + 3v_{2x} & = - 15 \\ \implies v_{2x} & = - \frac 53 \end{aligned}

Similarly, by conservation of p y p_y , we have:

m 1 v 1 y + m 2 v 2 y = m 1 u 1 y + m 2 u 2 y 2 v 1 y + 3 v 2 y = 2 ( 5 ) + 3 ( 1 ) = 7 v 2 y = 7 2 v 1 y 3 . . . ( 1 ) \begin{aligned} m_1v_{1y} + m_2v_{2y} & = m_1u_{1y} + m_2u_{2y} \\ 2v_{1y} + 3v_{2y} & = 2(5) + 3(-1) = 7 \\ \implies v_{2y} & = \frac {7-2v_{1y}}3 & ...(1) \end{aligned}

Now, consider the conversion of kinetic energy:

1 2 m 1 v 1 2 + 1 2 m 2 v 2 2 = 1 2 m 1 u 1 2 + 1 2 m 2 u 2 2 m 1 2 ( v 1 x 2 + v 1 y 2 ) + m 2 2 ( v 2 x 2 + v 2 y 2 ) = m 1 2 ( u 1 x 2 + u 1 y 2 ) + m 2 2 ( u 2 x 2 + u 2 y 2 ) ( 5 ) 3 + v 1 y 2 + 3 2 ( ( 5 3 ) 2 + v 2 y 2 ) = 3 2 + 5 2 + 3 2 ( ( 7 ) 2 + ( 1 ) 2 ) v 1 y 2 + 3 2 v 2 y 2 = 479 6 ( 1 ) : v 2 y = 7 2 v 1 y 3 v 1 y 2 + 3 2 ( 7 2 v 1 y 3 ) 2 = 479 6 10 v 1 y 2 28 v 1 y 430 = 0 \begin{aligned} \frac 12 m_1 v_1^2 + \frac 12 m_2 v_2^2 & = \frac 12 m_1 u_1^2 + \frac 12 m_2 u_2^2 \\ \frac {m_1}2 \left(v_{1x}^2 + v_{1y}^2\right) + \frac {m_2}2 \left(v_{2x}^2 + v_{2y}^2\right) & = \frac {m_1}2 \left(u_{1x}^2 + u_{1y}^2\right) + \frac {m_2}2 \left(u_{2x}^2 + u_{2y}^2\right) \\ (-5)^3 + v_{1y}^2 + \frac 32 \left(\left(-\frac 53\right)^2 + v_{2y}^2\right) & = 3^2 + 5^2 + \frac 32 \left((-7)^2 + (-1)^2\right) \\ v_{1y}^2 + \frac 32 \color{#3D99F6} v_{2y}^2 & = \frac {479}6 & \small \color{#3D99F6} (1): v_{2y} = \frac {7-2v_{1y}}3 \\ v_{1y}^2 + \frac 32 \color{#3D99F6} \left(\frac {7-2v_{1y}}3\right)^2 & = \frac {479}6 \\ \implies 10v_{1y}^2 - 28v_{1y} - 430 & = 0 \end{aligned}

Solving the quadratic equation for v 1 y v_{1y} and checking the respective kinetic energies E 1 E_1 and E 2 E_2 :

{ v 1 y = 8.105 v 2 y = 3.070 E 1 = 90.695 E 2 = 18.305 E 1 : E 2 5 : 1 Accepted. v 1 y = 5.305 v 2 y = 5.870 E 1 = 53.145 E 2 = 55.854 E 1 : E 2 1 : 1 Rejected. \begin{cases} v_{1y} = \color{#3D99F6} \boxed{8.105} & \implies v_{2y} = -3.070 & E_1 = 90.695 & E_2 = 18.305 & E_1:E_2 \approx 5:1 & \small \color{#3D99F6} \text{Accepted.} \\ v_{1y} = -5.305 & \implies v_{2y} = 5.870 & E_1 = 53.145 & E_2 = 55.854 & E_1:E_2 \approx 1:1 & \small \color{#D61F06} \text{Rejected.} \end{cases}

Thanks. Did you choose the positive root for v 1 y v_{1y} because of the stated energy ratio between Mass 1 and Mass 2?

Steven Chase - 2 years, 8 months ago

Log in to reply

Yes, I had mistaken that velocity could not be negative. I will amend the solution. Thanks.

Chew-Seong Cheong - 2 years, 8 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...